2007
DOI: 10.1039/b712798g
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen-17 hyperfine structures in the pure rotational spectra of SrO, SnO, BaO, HfO and ThO

Abstract: Hyperfine structures arising from the couplings of the nuclear spin angular momentum of (17)O (I = 5/2) with the end over end rotation of several metal-containing diatomic monoxides have been observed using a Fourier transform microwave spectrometer. The molecules have been produced by reacting (17)O(2) with laser ablated metal atoms. The oxygen-17 nuclear quadrupole coupling constants have been determined for the title molecules and are interpreted in terms of a simple Townes-Dailey model. Also, the oxygen-17… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…We have also included the recently recorded J = 1-0 rotational transition for 120 Sn 17 O [4]. The J = 1-0 rotational transition for 120 Sn 17 O displayed 17 O nuclear quadupole hyperfine structure, however using the constants of Ref.…”
Section: Dunham Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…We have also included the recently recorded J = 1-0 rotational transition for 120 Sn 17 O [4]. The J = 1-0 rotational transition for 120 Sn 17 O displayed 17 O nuclear quadupole hyperfine structure, however using the constants of Ref.…”
Section: Dunham Analysismentioning
confidence: 99%
“…Although SnO has been the subject of four prior microwave studies [1][2][3][4] and a high resolution infrared study [5], this type of hyperfine detail has not been observed. This is likely due to the high resolution required to observe magnetic hyperfine structure for diamagnetic species and also the low abundance of the odd-atomic-mass Sn isotopes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to obtaining very accurate molecular constants, these measurements demonstrate that the sensitive and versatile PPMODR technique can be readily applied to heavy element compounds over a wide frequency range. Prior to the results reported here, the only actinide containing molecules for which rotational transitions had been reported were ThO [5][6][7] and UO [8].…”
Section: Page 6 Of 16mentioning
confidence: 99%
“…While there have been several spectroscopic studies of the ground and low-lying electronic states, [3][4][5][6][7][8] In the present study we have measured the Stark effect for numerous branch features of the E(0 We also analyze the field-free spectrum to derive the bond distances for the E(0…”
mentioning
confidence: 99%